SIRPα1-SHP2 Interaction Regulates Complete Freund Adjuvant–Induced Inflammatory Pain via Src-Dependent GluN2B Phosphorylation in Rats. (March 2016) - Lai, Cheng-Yuan; Lin, Tzer-Bin; Hsieh, Ming-Chun; Chen, Gin-Den; Peng, Hsien-Yu
Abstract : BACKGROUND: The elusiveness of pain mechanisms is a major impediment in developing effective clinical treatments. We examined whether the signal regulatory protein α1 (SIRPα1)-activated spinal Src homology-2 domain-containing protein tyrosine phosphatase 2 (SHP2)/Src cascade and the downstream GluN2B phosphorylation play a role in inflammatory pain. METHODS: At hour 3 and days 1, 3, 5, and 10 after the intraplantar injection of complete Freund adjuvant (CFA), we assessed paw withdrawal latency using the Hargreaves test and analyzed dorsal horn samples (L4-L5) by Western blotting and immunoprecipitation. RESULTS: Intraplantar CFA injection provoked the behavioral hyperalgesia in the ipsilateral hind-paw along with SIRPα1, phosphorylated SHP2 (pSHP2), phosphorylated Src (pSrc), and phosphorylated GluN2B expressions and total SHP2 (tSHP2)-SIRPα1/pSHP2/pSrc and total Src (tSrc)-SIRPα1/pSHP2/pSrc coprecipitation in the ipsilateral dorsal horn. Although both of them failed to show an effect on CFA-enhanced SIRPα1 expression, spinal administration with SIRPα1-neutralizing antibody (10, 50, and 100 μg, 10 μL) and 8-Hydroxy-7-[(6-sulfo-2-naphthyl)azo]-5-quinolinesulfonic acid (NSC 8787; an SHP2 antagonist, 1, 10, and 100 μM, 10 μL) dose-dependently attenuated the behavioral hyperalgesia, SHP2 and Src phosphorylation, and tSHP2-SIRPα1/pSHP2/pSrc coprecipitation at day 1 after CFA injection. Intrathecal application of 4–amino–5–(4–chlorophenyl)–7–(t–butyl)pyrazolo[3, 4–d]pyrimidine (PP2; a Src-family kinase inhibitor, 10, 30, and 50 nM, 10 μL) exhibited a similar effect as these agents, except that it failed to ameliorate CFA-enhanced SHP2 phosphorylation and tSHP2-SIRPα1/pSHP2 coprecipitation. CONCLUSIONS: CFA-induced spinal SIRPα1 expression, which triggers SHP2, and Src phosphorylation, which subsequently induced pSrc-GluN2B interaction to mediate the GluN2B activation, contribute to spinal plasticity underlying the maintenance of inflammatory pain. These findings provide a possible strategy for pain relief by targeting to spinal SIRPα1-SHP2 coupling. Abstract : Published ahead of print December 30, 2015